2013
DOI: 10.5194/acp-13-4307-2013
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and spatial variability of the OM/OC mass ratios and high regional correlation between oxalic acid and zinc in Chinese urban organic aerosols

Abstract: We calculated the organic matter to organic carbon mass ratios (OM/OC mass ratios) in PM2.5 collected from 14 Chinese cities during summer and winter of 2003 and analyzed the causes for their seasonal and spatial variability. The OM/OC mass ratios were calculated two ways. Using a mass balance method, the calculated OM/OC mass ratios averaged 1.92 ± 0.39 year-round, with no significant seasonal or spatial variation. The second calculation was based on chemical species analyses of the organic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 53 publications
5
78
0
Order By: Relevance
“…OM was derived from multiplying OC concentrations by a factor of 1.6 to account for unmeasured atoms, such as hydrogen, oxygen, and nitrogen in organic materials. The factor of 1.6 was employed in this study according to Xing et al (2013), which demonstrated that the calculated OM/OC mass ratio in summer was relatively high (1.75 ± 0.13) and in winter was lower (1.59 ± 0.18) in PM 2.5 collected from 14 Chinese cities.…”
Section: Discussionmentioning
confidence: 99%
“…OM was derived from multiplying OC concentrations by a factor of 1.6 to account for unmeasured atoms, such as hydrogen, oxygen, and nitrogen in organic materials. The factor of 1.6 was employed in this study according to Xing et al (2013), which demonstrated that the calculated OM/OC mass ratio in summer was relatively high (1.75 ± 0.13) and in winter was lower (1.59 ± 0.18) in PM 2.5 collected from 14 Chinese cities.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that mineral elements contribute less (0.5%) to PM 2.5 (Zhang et al, 2012b). The ratio of organic matter (OM) to organic carbon (OM: OC) could vary from 1.4 to 2.0 in Beijing (Xing et al, 2013). Provided that OM equal to twice of OC, 13%, 19% and 20% of PM 2.5 could be defined as non-C atoms organic matters.…”
Section: Characterization Of Chemical Components During Different Polmentioning
confidence: 99%
“…Hence, a high OM / OC ratio indicates a high degree of oxidation of the organic aerosols and probably a high degree of hygroscopicity (Jimenez et al, 2009). There is a variety of methods that have been used to calculate OM / OC ratio as reported by Xing et al (2013). In our case, the ambient OM / OC ratio is calculated by weighting the ratio (OM/OC) i of each surrogate species i by the relative mass of the surrogate:…”
Section: Oxidation State Of Organicsmentioning
confidence: 99%